Late‐onset progressive retinal atrophy in the Gordon and Irish Setter breeds is associated with a frameshift mutation in C2orf71. (12th June 2012) - Downs, L. M.; Bell, J. S.; Freeman, J.; Hartley, C.; Hayward, L. J.; Mellersh, C. S.
Summary: Progressive retinal atrophy (PRA) in dogs is characterised by the degeneration of the photoreceptor cells of the retina, resulting in vision loss and eventually complete blindness. The condition affects more than 100 dog breeds and is known to be genetically heterogeneous between breeds. Around 14 mutations have now been identified that are associated with PRA in around 49 breeds, but for the majority of breeds the mutation(s) responsible have yet to be identified. Using genome‐wide association with 16 Gordon Setter PRA cases and 22 controls, we identified a novel PRA locus, termed rod–cone degeneration 4 ( rcd4 ), on CFA17 ( P raw  = 2.22 × 10 −8, P genome  = 2.00 × 10 −5 ), where a 3.2‐Mb region was homozygous within cases. A frameshift mutation was identified in C2orf71, a gene located within this region. This variant was homozygous in 19 of 21 PRA cases and was at a frequency of approximately 0.37 in the Gordon Setter population. Approximately 10% of cases in our study (2 of 21) are not associated with this C2orf71 mutation, indicating that PRA in this breed is genetically heterogeneous and caused by at least two mutations. This variant is also present in a number of Irish Setter dogs with PRA and has an estimated allele frequency of 0.26 in the breed. The function of C2orf71 remains unknown, but it is important for retinal development and function and has previously been associated with autosomal recessive retinitis pigmentosa in humans.